2020
DOI: 10.3390/ani10101882
|View full text |Cite
|
Sign up to set email alerts
|

The Concerns, Difficulties, and Stressors of Caring for Pets during COVID-19: Results from a Large Survey of U.S. Pet Owners

Abstract: Pets may be a positive presence for their owners during the Coronavirus Disease 2019 (COVID-19) pandemic. However, it is pertinent to identify the hardships associated with pet ownership. We conducted a large-scale survey of U.S. pet owners (n = 2254) in spring and summer 2020 to assess the ways that relationships with pets impacted life during COVID-19. We used thematic analysis to analyze 3671 open-ended responses to three prompts. Reported concerns fell into three major categories: (1) pet-focused (meeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
179
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 60 publications
8
179
2
1
Order By: Relevance
“…Eighty-four percent of respondents reported feeling more attuned to their pet's health, and 37% report paying more attention to their pet's care. Other recent studies have reported similar concerns in the United States as well as Spain and the United Kingdom ( 5 – 7 ).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Eighty-four percent of respondents reported feeling more attuned to their pet's health, and 37% report paying more attention to their pet's care. Other recent studies have reported similar concerns in the United States as well as Spain and the United Kingdom ( 5 – 7 ).…”
Section: Introductionsupporting
confidence: 65%
“…This situation was unprecedented, resulting in a great deal of anxiety and uncertainly about the future. This anxiety encompassed all areas of daily living, so it is not surprising that dog owners felt significant concerns related to providing for their dog, nor the fact that these concerns have been expressed by other dog owners in the United States as well as Spain and the United Kingdom ( 5 – 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A survey study in the US indicated that pet owners experienced unique hardships related to changes in everyday life from the COVID-19 pandemic. They also recommended that these hardships should be considered alongside the potential benefits of pet ownership in order to manage pet owner expectations, prevent pet relinquishment, and more fully understand multifaceted human-companion animal relationships ( Applebaum et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, studies also document stressors associated with caring for pets amidst the pandemic. A study based in the U.S. found that pet owners reported several forms of caretaking stress, such as the inability to socialize their pet, difficulties obtaining resources (e.g., food, litter, medication), and managing behavioral issues (e.g., barking, attention-seeking) that disrupted telework routines [ 21 ]. Further, a study of pet owners living in the U.S. found that owners who were more attached to their pet were more likely to report delaying COVID testing or treatment due to worries about their pet’s welfare [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also hypothesized that some of those with a less severe symptom profile (e.g., low, mild) at pre-COVID would transition to a more severe symptom profile, which is based on evidence that the pandemic has led to higher rates of depression and anxiety [ 4 , 5 , 6 , 7 , 8 ]. Finally, we expected that attachment to pets would predict changes in psychological adjustment based on prior research documenting both the negative and positive effects of HAI (e.g., [ 18 , 21 , 22 ]). We were not able to make any more specific predictions about the effects of attachment to pets on transitions in subgroup membership over time given that no prior HAI studies have utilized a person-centered approach to examine changes in psychological adjustment before and after the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%